1998
DOI: 10.1037/0012-1649.34.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic conceptions of moral maturity.

Abstract: In presenting this thesis in partial fulfilment of the requirements for an advanced degree at the University of British Columbia, I agree that the Library shall make it freely available for reference and study. I further agree that permission for extensive copying of this thesis for scholarly purposes may be granted by the head of my department or by his or her representatives. It is understood that copying or publication of this thesis for financial gain shall not be allowed without my written permission. Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
256
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(276 citation statements)
references
References 30 publications
11
256
0
6
Order By: Relevance
“…The moral behavior of interest was the intention to lie during the salary negotiation. Lying was chosen as a focal behavior because studies of moral prototypes show that honesty is among the traits that people use most frequently to define moral character (Aquino & Reed, 2002;Lapsley & Laskey, 2001;Walker & Pitts, 1998). Therefore, it seems reasonable to assume that telling a lie is likely to be experienced by most people as violating self-standards of what it means to be a moral person.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moral behavior of interest was the intention to lie during the salary negotiation. Lying was chosen as a focal behavior because studies of moral prototypes show that honesty is among the traits that people use most frequently to define moral character (Aquino & Reed, 2002;Lapsley & Laskey, 2001;Walker & Pitts, 1998). Therefore, it seems reasonable to assume that telling a lie is likely to be experienced by most people as violating self-standards of what it means to be a moral person.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of individual characteristics have been proposed as determinants of moral behavior, including moral reasoning (Kohlberg, 1969), moral maturity (Walker & Pitts, 1998), moral commitment (Colby & Damon, 1992), moral personality (Walker & Frimer, 2007), and moral character (Blasi, 2005). Previous research generally finds that these characteristics are associated with moral behavior to varying degrees, but none appears fully capable of predicting or accounting for situational variability in moral behavior (Hardy & Carlo, 2005;Shao, Aquino, & Freeman, 2008).…”
Section: A Social-cognitive Conception Of Moral Identitymentioning
confidence: 99%
“…Elevados factores altos se presentaron asociados con un funcionamiento óptimo y bajos factores altos se presentaron asociados con un funcionamiento relacionado, en última instancia, a la patología. Si bien la idea de continuidad sindrómica no es nueva, muy pocos modelos psicológicos han vinculado la salud y la enfermedad de forma conjunta (e.g., Leary, 1957;Millon, 1996;Millon & Everly, 1994;Offer & Sabshin, 1991;Strack & Lorr, 1994). El modelo de personalidad de Millon y el abordaje del continuo salud-enfermedad del modelo de Keyes son dos importantes excepciones.…”
Section: Discussionunclassified
“…The prototype of the just person was described as a moderate blend of nurturance and dominance, and aligned with conscientiousness and openness to experience. An earlier study (Walker & Pitts, 1998) reported a relationship between trait dimensions and three kinds of moral exemplars. The brave exemplar was linked with a complex of traits associated with extraversion; the caring exemplar was associated with agreeableness; while the just exemplar was a complex mixture of conscientiousness, emotional stability, and openness to experience.…”
Section: Models Of Personality Psychologymentioning
confidence: 99%
“…Similarly, Walker (2004;Walker & Pitts, 1998) has pursued naturalistic studies of the prototype structure of a " highly moral person" and has identified clusters or themes that commonly show up in people's understanding of moral maturity. One cluster, for example, is a set of "principled-idealistic" commitments to strongly held values.…”
Section: Bag Of Virtues and Foundationsmentioning
confidence: 99%